Modern methods of reclamation of disturbed land landscape in terms of open-pit mining of horizontal deposits - Malieiev, Ye.V. (Геотехнічна механіка, 2017)
The article presents analysis of current techniques used for landscape reclamation and water-exchange process restoration in the disturbed geological environment in the process of the dump formation and reclamation at excavating of horizontal and flat-dipping deposits. Interrelations between directions of the quarry face advancement and streams of surface and ground water flows as well as their influence on efficiency of technological processes of the open-pit mining operations were determined. The determined expedient direction of the quarry face advancement makes it possible to restore the surface relief to the level almost similar to the natural one. Scheme of layer-by-layer technical and biological reclamation of the disturbed lands for their further use in agriculture is represented. В статті розглянуто сучасні способи відновлення ландшафту і водообмінних процесів у порушеному геологічному середовищі в процесі відвалоутворення і рекультивації при відкритій розробці горизонтальних і пологопадаючих родовищ. Встановлені взаємозв'язки між напрямками переміщення фронту гірничих робіт кар'єру і потоком поверхневих і підземних вод, їх вплив на ефективність технологічних процесів відкритої розробки. Визначено раціональний напрямок переміщення фронту гірничих робіт, що дозволяє відновити рельєф поверхні у вигляді, близьким до природного. Приведено схему пошарової гірничотехнічної та біологічної рекультивації порушених земель для подальшого використання їх у сільському господарстві. В статье рассмотрены современные способы восстановления ландшафта и водообменных процессов в нарушенной геологической среде в процессе отвалообразования и рекультивации при открытой разработке горизонтальных и пологопадающих месторождений. Установлены взаимосвязи между направлениями перемещения фронта горных работ карьера и потоком поверхностных и подземных вод, их влияние на эффективность технологических процессов открытой разработки. Определено рациональное направление перемещения фронта горных работ, которое позволяет восстановить рельеф поверхности в виде, близким к природному. Приведена схема послойной горнотехнической и биологической рекультивации нарушенных земель для дальнейшего использования их в сельском хозяйстве.